Understanding and addressing the Schoolies phenomenon. (25th February 2015) - Pettigrew, Simone; Biagioni, Nicole; Daube, Mike; Jones, Sandra C.; Chikritzhs, Tanya; Kirby, Gary
Abstract Objective: This study qualitatively explored Western Australian school leavers' alcohol‐related experiences during the Schoolies period to generate insights for the purpose of intervention design. This is in the context of an impending change in the age of Western Australian students completing secondary school which, for the first time, will see around half being of legal age to purchase alcohol. Method: Fifty‐four 18–21‐year‐olds provided reflections via an emailed introspection on their experiences in the immediate post‐school period. This provided access to the views of those who chose to attend events and consume large amounts of alcohol, those who attended events but refrained from excessive alcohol consumption, and those who elected to either avoid Schoolies events or engage in alternative celebrations. The data were coded and analysed using NVivo10. Results: Three primary themes were identified that related to the perceived role of alcohol during Schoolies, the range of associated rite‐of‐passage rituals, and the strategies used by some Leavers to avoid alcohol and its consequences during the Schoolies period. Conclusion: Students and parents constitute important target groups for interventions designed to address alcohol‐related harms during Schoolies. In the WA context, legislation on secondary supply and controlled purchase, as recommended by health and police authorities, could reduce harms that are likely to result from the change in the age of school leavers. Suggestions for alternative pastimes to promote to school leavers are provided.